The "backdoor pathway" of androgen synthesis in human male sexual development. - Walter L Miller; Richard J Auchus (PLoS Biology, 2019)
Mammalian sex determination (male versus female) is largely controlled by genes, whereas sex differentiation (development of reproductive structures) is largely controlled by hormones. Work in the 20th century indicated that female external anatomy was a "default" pathway of development not requiring steroids, whereas male genital development required testicular testosterone plus dihydrotestosterone (DHT) made in genital skin according to a "classic" pathway. Recent work added the description of an alternative "backdoor" pathway of androgen synthesis discovered in marsupials. Unique "backdoor steroids" are found in human hyperandrogenic disorders, and genetic disruption of the pathway causes disordered male sexual development, suggesting it plays an essential role. O'Shaughnessy and colleagues now show that the principal human backdoor androgen is androsterone and provide strong evidence that it derives from placental progesterone that is metabolized to androsterone in nontesticular tissues. These studies are essential to understanding human sexual development and its disorders.